Multilingual Joint Training Enhances Adversarial Robustness in PAWS-X for Mid-Sized Transformers - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 13 peer-reviewed papers addressing the following research question: Does joint training on English and Indonesian datasets improve robustness against adversarial perturbations in PAWS-X compared to single-language fine-tuning for mid-sized multilingual transformers. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 6.7/10. This report i
Machine-generated literature synthesis.